From invisibility to recognition: “Work” in the materialist tradition and in contemporary feminist debates - Bolla, Luisina (2025)
This article links the materialist tradition with contemporary debates about labor, in the area of feminist and gender theories. In particular, it focuses on discussions about the value of labor traditionally performed by women and the difficulties involved in their full recognition. Certain locus - double shift, sociosexual division of labor, invisibility - reappear insistently and cross different periods, allowing a diachronic approach that shows both the lucidity of the arguments of classical feminists such as the validity of these problems and the need for their critique. This implies knotting economic and ethical dimensions - as Fraser says, problems of redistribution, recognition and representation- that ultimately lead to a reflection on social justice.